Effects of training in intermediate altitude by two national U20 CONCACAF soccer teams - Ventura Franco, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
University Football and Sports Science (UFD) Hidalgo Mexico. 2: Center for Medical Excellence of Altitude (CEMA) Introduction. Science seeks to explain the physiological changes that occur in athletes in response to different altitudes. The aim of this study was to measure the effect of training in an altitude of 2520 meters above sea level, from biomedical test applied to the U 20 football teams; who prepared for U20 qualification world cup. Methods: A comparative of the results of study 1) hemoglobin (Hb) and red blood cells, 2) to establish Electrocardiogram adaptation anaerobic to aerobic sport, 3) score of Lake Louis, which assesses the degree of illness of AMS (Acute Mountain Sickness). Classified according to score: MAM MILD: 1 to 3 points. MAM MODERATE: 4 to 6 points, MAM GRAVE: 7 points or more. Including 20 players from two U20 selections, one from an average altitude of 1300 meters above sea level (Team 1) and another from sea level (Team 2). Results: 18 players from Team 1 with mean age of 18.8 + 0.61, with an average initial (hb) with respect to the final (hb) not present significance (p = 0.38), similar result was presented at the level of red blood cells (p = 0.50), According to the index of initial Chignon 13 players presented leveled systems, 4 with predominantly anaerobic and 1 aerobic dominance. At the end we found 8, 10 and 0 players respectively. The Lake Louise tests only 2 players show MAM mild and one moderate. Team 2 was evaluated (n = 20), with a mean age of 18.9 +/- 0.9, and an initial average (hb) level of 14.6 and 15.9 at the end the difference was significant (p = 0.0023). The number of erythrocytes cells at the training period incremented from 4947.0 to 5553.5 (p = 0.01); The Chignon index showed 18 players with leveled anaerobic systems, and one with anaerobic aerobic dominance, which was modified to 9, 6 and 5 respectively. The Lake Louise test 10 days after the stay detected 10 players with MAM Mild and MAM 6 moderate the rest showed no alteration. Discussion: According to the above it was shown that for the Team 2 coming from sea level, was sufficient 10 days to improve (hb) levels. Also it showed more evident acute mountain sickness, although none of the athletes presented severely. Regarding the rate anaerobic - aerobic the adaptation was more evident in the athletes from Team 1.